Advocating for incorporating public veterinary health care into human health systems - Meythaler-Mullins, Laurie; Eia, Cheryl; Lobdell, Allyce H.; Frey, Danielle M. (Frontiers in Veterinary Science, 2025)
In the first study to examine veterinary services in rural Alaska, this paper focuses on the use of a public health veterinary program embedded in the human health care system as a means of improving human health, specifically in rural villages such as the Yukon-Kuskokwim Delta of Alaska (YK Delta). The YK Delta is home to approximately 23,000 people living in 58 distinct rural communities, each of which is a federally recognized Tribe. Dogs play a particularly important role in these tribal communities. However, access to veterinary services is extremely limited in the region. Bringing together data from the Hub Outpost Project (HOP) which was designed to deliver preventative, public health veterinary services throughout the region, a meta-synthesis on relevant topics in similarly situated regions, and cost data, this paper examines three critical veterinary public health issues affecting the YK Region: (1) human exposures to rabies, (2) dog bite injuries and dog overpopulation, and (3) how a veterinary preventative medicine program like HOP can provide a cost-effective way to improve human health and reduce the cost to individuals and the community from these risks. The HOP model demonstrates effective and consistent veterinary preventative care in that it increased the number of vaccinated dogs, thereby reducing rabies exposure risk to humans. As demonstrated in this paper, the authors believe the education and population control provided by programs like HOP can decrease the number of dog bites and dog overpopulation. The authors strongly advocate for the implementation of this One Health model of veterinary service within the established human health system to maintain consistency and effectiveness.